Haikyu!! 3-in-1 edition. 4-5-6 - Furudate, Haruichi, 1983- (Shonen Jump manga., 2024)
Ever since he saw the legendary player known as "the Little Giant" compete at the national volleyball finals, Shoyo Hinata has been aiming to be the best volleyball player ever! Who says you need to be tall to play volleyball when you can jump higher than anyone else? Karasuno's training camp kicks off with a bang, and the moment they've all been waiting for finally arrives--the revival of the long-standing rivalry between the Cats and the Crows! Karasuno's practice games against Nekoma reveal all the cracks in their teamwork, and they'd better patch things up if they're to stand a chance in the Inter-High qualifiers. Team Karasuno realizes that their chances are even slimmer when they see who they're up against in their block: Aoba Johsai and the Iron Wall of Date Tech!